A non-classical optimal control problem - Wan Ahmad, Wan Noor Afifah; Sufahani, Suliadi Firdaus; Rusiman, Mohd Saifullah; Ali, Maselan (UTHM Publisher, 2018)
We consider another non-classical of optimal control problem that is spurred by some current research on the nonlinear income issue in the field of financial matters. This class of issue can be set up as a maximizing issue in the area of Optimal Control. In any case, the state value at the final fixed time, y(T), is priori unknown and the integrand is an element of the unknown y(T). This is a non-classical optimal control problem. In this paper we apply the new costate value conditions p(T) in the definition of the optimal control problem. We solve some examples in this issue using the numerical shooting method to illuminate the subsequent Two Point Boundary Value Problem (TPBVP) and join the free y(T) as an additionally unknown. Basically similar outcomes are obtained through the nonlinear programming (NP) discrete-time results.